Intepirdine as adjunctive therapy to donepezil for mild‐to‐moderate Alzheimer's disease: A randomized, placebo‐controlled, phase 3 clinical trial (MINDSET). Issue 1 (31st May 2021) - Lang, Frederick M.; Mo, Yi; Sabbagh, Marwan; Solomon, Paul; Boada, Merce; Jones, Roy W.; Frisoni, Giovanni B.; Grimmer, Timo; Dubois, Bruno; Harnett, Mark; Friedhoff, Sarah R.; Coslett, Shari; et al.
Abstract: Introduction: A previous phase 2b study supported the use of the 5‐HT6 receptor antagonist intepirdine as adjunctive therapy to donepezil for Alzheimer's disease (AD) dementia. A phase 3 study, MINDSET, was performed to test this hypothesis. Methods: MINDSET was a global, double‐blind, randomized, placebo‐controlled trial in 1315 mild‐to‐moderate AD dementia patients on stable donepezil. Patients received 35 mg/day intepirdine or placebo for 24 weeks. The co‐primary endpoints were change from baseline to week 24 on the Alzheimer's Disease Assessment Scale‐Cognitive Subscale (ADAS‐Cog) and Alzheimer's Disease Cooperative Study‐Activities of Daily Living (ADCS‐ADL). Results: There were no statistically significant differences between intepirdine and placebo groups (adjusted mean [95% confidence interval]) on the co‐primary endpoints ADAS‐Cog (−0.36 [−0.95, 0.22], P = 0.2249) and ADCS‐ADL (−0.09 [−0.90, 0.72], P = 0.8260). Intepirdine demonstrated a favorable safety profile similar to placebo. Discussion: Intepirdine as adjunctive therapy to donepezil did not produce statistical improvement over placebo on cognition or activities of daily living in mild‐to‐moderate AD dementia patients.